An in vitro explant model for studies of intestinal amino acid metabolism. (February 2020) - Pestour, Sandie; Couchet, Morgane; Breuillard, Charlotte; Corne, Christelle; Mathieu, Nicolas; Lamarche, Frédéric; Fontaine, Eric; Coëffier, Moïse; Moinard, Christophe
Summary: Background & aims: The main role of the small intestine to absorb the bulk of dietary nutrients, including proteins and amino acids (AA). Enterocytes have long been considered a major player in amino acid homeostasis, especially the glutamine–citrulline–arginine crossroads. In vivo intestinal epithelium cell lines for studies of nitrogen metabolism have now reached their limitations. To push research forward, an interesting approach could be to use the explant incubation model of intestinal tissue, involving in vitro incubation of duodenal tissue biopsy specimens taken from human subjects. Methods: Eight duodenal biopsies were taken during endoscopy from patients without proven intestinal disease. Each biopsy was incubated in complete culture medium for 23 h then weighed, and cell viability was evaluated after 6 and 18 h. We then explored L-citrulline (L-CIT) production (reflecting metabolic activity) and the presence of the main enzymes involved in AA metabolism in the intestine (arginase II, glutaminase I, ornithine aminotransferase, and ornithine carbamoyltransferase). Results: Mean weight of biopsies was 12.36 ± 1.00 mg. Mortality was around 20% after 6 h and 50% after 18 h of incubation. CIT was amply produced by the biopsies, and enzymes implicated in intestinal AA metabolism were expressed in this model. Conclusions: This in vitro explant model of intestinal tissue emerges as a reliable model for conducting ex vivo investigations on AA metabolism.